2015
DOI: 10.4238/2015.december.21.15
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the association between NLRP3 gene polymorphisms and susceptibility to type 2 diabetes mellitus

et al.

Abstract: ABSTRACT. We conducted a case-control study to investigate the role of three common polymorphisms (rs10754558, rs7512998, and rs12137901) of the gene NLR family, pyrin domain containing 3 (NLRP3) in the development of type 2 diabetes mellitus (T2DM). Between May 2013 and May 2014, 385 patients with T2DM and 401 control subjects were enrolled in our study. Genotyping of the three NLRP3 polymorphisms of interest was performed by polymerase chain reaction-restriction fragment length polymorphism. Unconditional lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…For example, PPP1R3B, which was differentially methylated in our study, codes for the G L regulatory subunit of protein phosphatase 1 (PP1), which targets PP1 to activate glycogen synthase, thereby increasing insulin sensitivity of liver and skeletal muscle [35,36]. A decreased rate of glycogen synthesis in the skeletal muscle in response to insulin is a characteristic feature of individuals with type 2 diabetes [37], and polymorphisms in another regulatory subunit (PPP1R3A), which also targets PP1 activation of glycogen synthase in the skeletal muscle, were associated with insulin resistance and type 2 diabetes in several different populations [38][39][40][41][42]. Differential methylation of a second gene, PM20D1, could also affect insulin sensitivity via its effect on body weight.…”
Section: −5mentioning
confidence: 99%
“…For example, PPP1R3B, which was differentially methylated in our study, codes for the G L regulatory subunit of protein phosphatase 1 (PP1), which targets PP1 to activate glycogen synthase, thereby increasing insulin sensitivity of liver and skeletal muscle [35,36]. A decreased rate of glycogen synthesis in the skeletal muscle in response to insulin is a characteristic feature of individuals with type 2 diabetes [37], and polymorphisms in another regulatory subunit (PPP1R3A), which also targets PP1 activation of glycogen synthase in the skeletal muscle, were associated with insulin resistance and type 2 diabetes in several different populations [38][39][40][41][42]. Differential methylation of a second gene, PM20D1, could also affect insulin sensitivity via its effect on body weight.…”
Section: −5mentioning
confidence: 99%
“…The inflammasome, can be activated by metabolic damage and by infection, has also been proposed to be involved in the pathogenesis of periodontal disease and T2D (Huang et al, ). Inflammasome activation by pathogen‐associated molecular patterns (PAMPs) or by host‐derived danger‐associated molecular patterns (DAMPs) incites a conformational change in the multi‐protein complex and triggers the activation of caspase‐1 and ‐5, proteases required for the activation of pro‐inflammatory cytokines IL‐18 and IL‐1β (Wang, Fang, Jin, Wang, & Zheng, ; Xue, Shu, & Xie, ). NLR family pyrin domain containing 3 (NLRP3) is the most studied and characterised inflammasome, and it contains the adaptor protein apoptosis‐associated speck like protein (ASC) (Schroder, Zhou, & Tschopp, ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasome activation by pathogen-associated molecular patterns (PAMPs) or by host-derived danger-associated molecular patterns (DAMPs) incites a conformational change in the multi-protein complex and triggers the activation of caspase-1 and -5, proteases required for the activation of pro-inflammatory cytokines IL-18 and IL-1β (Wang, Fang, Jin, Wang, & Zheng, 2015;Xue, Shu, & Xie, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prospective clinical relevance of this strategy is also supported by recent investigations on the influence of genetic variability in inflammasome on longterm cardiovascular complications in diabetic patients. A few studies have reported a relationship between NLRP3 genetic polymorphisms and development of type 2 diabetes [189,190] and, most notably, a specific polymorphic NLRP3 allele has been reported to be associated with increased risk for development of macrovascular complications in subjects with long-term diabetes [191].…”
Section: Nlrp3 Inflammasome Inhibitors -mentioning
confidence: 99%